Impact of treatment strategies for AF on the progression and regression of AF type in the CABANA trial. (25th November 2020) - Packer, D.L; Monahan, K.H; Piccini, J.P; Al-Khalidi, H.R; Silverstein, A.P; Poole, J.E; Bahnson, T.D; Mark, D.B
Abstract: Background: The CABANA trial compared drug vs ablation therapy yet did not identify a difference in the primary endpoint of death, stroke, severe bleeding, or cardiac arrest or the secondary endpoint of all-cause mortality by intention to treat (ITT) analysis. Nevertheless, there was evidence of improved outcomes and survival in the as-treated and per-protocol analyses. Objectives: To determine how the treatment strategies of drug therapy vs ablation impact the atrial fibrillation progression and regression. Methods: CABANA randomized 2204 pts with AF ≥65 yrs old or <65 with ≥1 risk factor for stroke at 126 sites worldwide to ablation with pulmonary vein isolation vs drug including rate/rhythm control medication. AF type was recorded at the time of enrollment in the CABANA Trial. Following treatment with drug therapy or ablation, the AF type was assessed as recorded at the patient's last follow-up. Comparisons between baseline AF type and last AF type were performed according to ITT. Results: Following treatment with ablation, 64% maintained sinus rhythm with elimination of AF, 11% experienced AF regression, and only 7% had progression of AF. In contrast, in those randomized to drug therapy, only 48% experienced maintenance of sinus rhythm, 10% experienced AF regression, and 13% had progression of AF. Moreover, in the drug arm there was a 32% increase in long-standing persistent compared with a 49% reduction in the ablation arm. Conclusion: Catheter ablation significantly alters the natural history of atrial fibrillation. Intention to treat analysis reveals that catheter ablation provides superior elimination of AF, protection against AF progression, and dramatically lower risks of long-standing persistent AF. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Institutes of Health